2016
DOI: 10.1111/psyp.12782
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of mindfulness during pregnancy on maternal autonomic nervous system function and infant development

Abstract: Mindfulness is known to decrease psychological distress. Possible benefits in pregnancy have rarely been explored. Our aim was to examine the prospective association of mindfulness with autonomic nervous system function during pregnancy and with later infant social-emotional development. Pregnant women (N = 156) completed self-report mindfulness and emotional distress questionnaires, and had their autonomic function assessed in their first and third trimesters, including heart rate (HR), indices of heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 91 publications
(109 reference statements)
1
51
0
2
Order By: Relevance
“…Mental and physical discomfort may disrupt or even alter an individual's ability of awareness and nonjudgment [11,33]. Braeken et al reported pregnant women with lower emotional disorders have higher mindfulness during prenatal and postpartum periods [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mental and physical discomfort may disrupt or even alter an individual's ability of awareness and nonjudgment [11,33]. Braeken et al reported pregnant women with lower emotional disorders have higher mindfulness during prenatal and postpartum periods [10].…”
Section: Discussionmentioning
confidence: 99%
“…The human attachment relationship originated from the work of Symptoms during Pregnancy. Arch Nurs Pract Care 5(1): 001-007. http://dx.doi.org/10.17352/anpc.000035 many studies have initiated psychological activities such as mindfulness interventions to reduce health problems during pregnancy [10,11]. It is wondering whether the mindfulness is obtained by training or naturally present without effort.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the literature about the effects of mindfulness training on mothers with babies is scarce, there is some scientific support for the benefits that mindfulness might have for mothers and babies. Maternal mindfulness during pregnancy has not only shown to be associated with less maternal prenatal and postnatal emotional distress but also with better social-emotional development of their babies (Braeken et al 2016 ; Van den Heuvel et al 2015a ), less difficult infant temperament, and improved infant neurodevelopmental outcomes (Van den Heuvel et al 2015a , b ). Also, postnatal mindfulness in parenting (not mindfulness in general) has shown to be predictive of infant stress regulation.…”
Section: Introductionmentioning
confidence: 99%